2017
DOI: 10.3389/fpls.2017.00365
|View full text |Cite
|
Sign up to set email alerts
|

Sub-high Temperature and High Light Intensity Induced Irreversible Inhibition on Photosynthesis System of Tomato Plant (Solanum lycopersicum L.)

Abstract: High temperature and high light intensity is a common environment posing a great risk to organisms. This study aimed to elucidate the effects of sub-high temperature and high light intensity stress (HH, 35°C, 1000 μmol⋅m-2⋅s-1) and recovery on the photosynthetic mechanism, photoinhibiton of photosystem II (PSII) and photosystem I (PSI), and reactive oxygen (ROS) metabolism of tomato seedlings. The results showed that with prolonged stress time, net photosynthetic rate (Pn), Rubisco activity, maximal photochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 54 publications
6
61
0
1
Order By: Relevance
“…With the severity of stress, photosynthetic ability, RuBisCO activity, quantum yield and 435 electron transport disrupted in tomato [137]. When plants face insufficient K supply leaf chlorosis 436 increased at high light [6].…”
Section: Hight Light 432mentioning
confidence: 99%
“…With the severity of stress, photosynthetic ability, RuBisCO activity, quantum yield and 435 electron transport disrupted in tomato [137]. When plants face insufficient K supply leaf chlorosis 436 increased at high light [6].…”
Section: Hight Light 432mentioning
confidence: 99%
“…However, these combined stresses can occur in tropical regions even without heat waves, especially in the summer. The isolated effects of high temperatures include altering the plants photosynthetic capacity, particularly by affecting membrane permeability, reducing the content of chloroplastidic pigments, and disrupting electron transport (Ashraf and Harris, 2013;Lu et al, 2017;Mishra et al, 2017). This disruption induces the formation of reactive oxygen species (ROS), which may promote photo-inhibition, as well as inactivation of Calvin cycle proteins and enzymes (Mathur et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chl fluorescence measurement can be used to assess changes of PSII photochemistry, linear electron flux, and CO2 assimilation in vivo (Maxwell andJohnson 2000, Baker 2008). Lu et al (2017) demonstrated that the photosynthetic capacity of tomato plants declines gradually and then sharply with leaf senescence under heat stress. During this process, the cell structure, metabolism, and gene expression of leaf cells undergo reversible or irreversible changes.…”
Section: Introductionmentioning
confidence: 99%